Skeletal muscle myostatin gene expression and sarcopenia in overweight and obese middle‐aged and older adults. Issue 4 (23rd September 2021) - Ryan, Alice S.; Li, Guoyan
Abstract: Background: Myostatin (MSTN) is a key negative regulator of muscle mass in humans and animals, having direct and indirect influences on molecular regulators of atrophy and hypertrophy, thus potentially impacting fitness and physical function. We have shown that myostatin is elevated in conditions of chronic disability (e.g. paretic limb of stroke). Our hypothesis is that myostatin would be elevated in older adults with sarcopenia. The purpose of this study was to examine the role of skeletal muscle myostatin in sarcopenia. Methods: Sixty‐four overweight to obese aged 45–81 years underwent a maximal aerobic capacity (VO2 max) test, dual‐energy X‐ray absorptiometry (DXA) scan to determine appendicular lean tissue (ALM), and vastus lateralis muscle biopsy to determine myostatin mRNA expression by quantitative real time PCR (Q‐RT‐PCR). Rates of sarcopenia were determined using (ALM/BMI), and sarcopenia was defined as <0.789 in men and <0.512 in women. Subjects had low fitness (VO2 max: 22.7 ± 0.7 mL/kg/min) and on average 40.9 ± 1% body fat. Results: The prevalence of sarcopenia in this cohort was 16%. BMI, % body fat, and fat mass were higher in adults with sarcopenia than those without sarcopenia (all P < 0.001). Myostatin mRNA expression was lower in those without sarcopenia than those with sarcopenia ( P < 0.05) and higher in men than women ( P < 0.001). Myostatin expression was associated with BMI ( r = 0.36, P < 0.01) and mid‐thigh intramuscular fat ( r = 0.29, P < 0.05). Conclusion: Given that myostatin is important in muscle atrophy, fat accumulation, and sarcopenia, further work could address its implication in other aging cohorts of disability and chronic disease.